Elaboração de um manual técnico nutricional para o atendimento de indivíduos com deficiência visual - MEIRELES, Renata Karoline da Silva (2023)
Visual impairment includes loss of total vision (blindness), reduced ability to see clearly (low vision). Among the activities of daily living (ADL's) that are most compromised by lack of vision are activities that involve eating. This study aims to develop a nutritional technical manual for the nutritionist's use to provide nutritional guidance for the management of visually impaired individuals. This is a descriptive study with a qualitative approach and bibliographic research. The elaboration of the manual is divided into two stages: contextualization and development. The contextualization is based on the literature review in studies published from 2005 to 2019 on the subject. Based on the guidelines of the Food Guide for the Brazilian Population (2014), Food and Nutrition Education strategies were created, which professionals can apply to nutritional care, helping these individuals with the purchase, organization and preparation of food. The manual covered topics such as: the conceptualization of vision and visual impairment, the importance of the nutritionist in the food and nutrition education of the visually impaired and the techniques that can help this public to deal with eating activities, as well as the tools to use it. in nutritional care through food and nutrition education. Elaborated the nutritional technical manual that will assist the nutritionist in the management of visually impaired people, promoting autonomy, food safety and the health maintenance of the studied public.